Estrus detection and its impact on reproductive and economic performance in large dairy herds - Fodor, István; Ózsvári, László (Animal welfare, Ethology and Housing Systems (AWETH), 2019)
Poor estrus expression is one of the major reasons of reproductive inefficiency on large dairy farms. Farm managers usually try to overcome this difficulty by using various estrus detection aids (e.g. pedometers, accelerometers, tail chalk), however, each method has its own limitations. Estrus detection aids generally lead to increased heat detection rate, better timing of inseminations relative to the time of ovulation, and ultimately, improved pregnancy rate. Some studies, however, did not find any benefit from the use of estrus detection aids, which is explained by (1) using the same rules on when to start inseminating heifers and cows as prior to the introduction of the new technology, and (2) by the widespread use of hormonal synchronization protocols that can potentially mask the effect of estrus detection aids. Economic outcome of the investment into estrus detection aids depends on the circumstances of the farm, although the reduction of labour cost can usually be expected. Despite efforts made towards the development of new estrus detection technologies, due to the high prevalence of anovular cows hormonal protocols are still required.
Keywords: dairy cattle; estrus detection; pedometer; activity monitoring; reproduction; economics